Rangelands Atlas Local Voices: Joint village land use planning in Tanzania - Olesikilal, Birikaa (International Livestock Research Institute, 2021)
Kiteto District Livestock Officer Birikaa Olesikilal talks about the benefits of joint village land use planning and participatory rangeland management, Tanzania. Filmed by Marco Buemi http://www.marcobuemi.com Produced by Fiona Flintan, Marco Buemi and Patrick Augenstein 2021